Parole revocation in South Africa: perspectives of adult male parole violators - Louw, Francois (Acta criminologica, 2019)
In South Africa, limited research exists regarding the parole revocation process and the parole revocation hearing is, so to speak, hidden from public view. In this article findings are presented from a mixed methods research study that explored parole violators’ perspectives on parole revocation. The study involved the collection and analysis of primarily quantitative data from self-administered questionnaires and was complemented by a qualitative data collection phase consisting of focus group interviews. The parole violators who participated in the study shared invaluable information about their experiences regarding parole and the parole revocation process. In practice, there is a noticeable inconsistency in dealing with parole violations. One offender may have a record of numerous technical violations and still be on parole, while another offender may have parole revoked after a minor technical violation. The research findings revealed the importance of graduated responses to parole violations that are fair, consistent, and legal.